Safety, Tolerability, and Pharmacokinetics of Single‐ and Multiple‐Ascending Doses of Sunobinop in Healthy Participants - Cipriano, Alessandra; Kapil, Ram P.; Zhou, Mingyan; Shet, Manjunath S.; Whiteside, Garth T.; Willsie, Sandra K.; Harris, Stephen C. (Clinical pharmacology in drug development, 2024)
Sunobinop is an investigational, potent, selective partial agonist at the nociceptin/orphanin FQ peptide receptor in vitro. Three phase 1 studies were conducted to evaluate the safety, tolerability, and pharmacokinetics (PK) of escalating single‐ and multiple‐dose administration of sunobinop in healthy participants. Study 1 was a randomized, double‐blind, placebo‐controlled, single‐ascending dose study. Study 2 was a randomized, double‐blind, placebo‐controlled, multiple‐ascending dose study. Study 3 was a randomized, open‐label, single‐dose, 4‐way crossover study of oral and sublingual sunobinop comparing morning (AM) and bedtime (PM) administration. Seventy participants were included. Systemic exposure (peak plasma concentration [Cmax], area under the plasma concentration‐time curve from time 0 to the time of last quantifiable concentration [AUC0‐t], and area under the plasma concentration–time curve from time 0 extrapolated to infinity [AUCinf]) of sunobinop was characterized by dose proportionality from 0.6 to 2 mg and increased less than proportionally from 3 to 30 mg. The PKs of sunobinop were similar, regardless of AM or PM administration, for both the oral and sublingual formulations. The majority of absorbed sunobinop was excreted unchanged in the urine within 8 hours of dosing, thereby showing rapid elimination with no appreciable accumulation following 14 consecutive days of once‐daily dosing and suggesting exclusive renal elimination. Most treatment‐emergent adverse events (TEAEs) were mild in severity; 1 severe TEAE occurred and all TEAEs resolved by the end of the studies. Sunobinop was generally well‐tolerated and safe across the range of doses evaluated and presents a clinical profile suitable for continued development.